Domestic Violence During The COVID-19 Pandemic - Toprak Ergönen, Akça; Biçen, Emin; Ersoy, Gökhan (The Bulletin of Legal Medicine, 2020)
Major outbreaks cause alterations in the dynamics of society. One of the leading is the change in crime trends. Although a significant decrease is observed in the total number of crimes, the frequency of some types of crime decreases while others increase, such as domestic violence. Although the number of systematic studies is not enough, data are showing that increased cases of violence against women during the COVID-19 outbreak in Turkey. Compared to the previous year, in March 2020, physical violence, psychological violence, and shelter demand increased by 80%, 93%, and 78%, respectively. Another survey-like study reported that there was a 27.8% increase in violence against women in the pandemic process. However, the number of child abuse cases decreased during this period. The difficulty of the detection of such cases due to social restriction may lead to this effect. These restrictions and the fear environment may also increase the risk of elder abuse and neglect. It’s important to take necessary measures to reduce the negative effects of long-term restraint in the quarantine period. In this review, we discussed the increase of domestic violence during the COVID-19 pandemic by presenting the available data. We also aimed to discuss the possible reasons for the increase in violence and the recommendations made by international and national organizations in solving the problem.